DEMAND AND ASSOCIATED FACTORS FOR PARTICIPATION IN CONTINUING MEDICAL EDUCATION THROUGH A BLENDED LEARNING MODEL AMONG TRADITIONAL MEDICINE HEALTHCARE WORKERS IN CAN THO CITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the demand and analyze factors associated with the willingness to participate in continuing medical education delivered through a blended learning model (online distance combined with face-to-face) among traditional medicine healthcare workers in Can Tho city. Subjects and methods: A cross-sectional analytical study was conducted among 245 traditional medicine healthcare workers in Can Tho city from May to September 2025.Results: The demand for continuing medical education was high, particularly for professional clinical content (mean score = 4.35 ± 0.69). Highly prioritized topics included new techniques, acupuncture, and updated treatment approaches. The demand for professional skills and management-legal training was also substantial (mean score > 4.0). Logistic regression analysis showed that course content (OR = 2.38; 95% CI: 1.01-5.60), cost, and institutional reputation were significantly associated with willingness to participate (p < 0.05). Exploratory factor analysis identified two main factors, explaining 80.259% of the total variance, with Cronbach’s Alpha coefficients > 0.9.Conclusion: Traditional medicine practitioners in Can Tho city have a high demand for continuing education. Course content, cost, and the reputation of the organizing institution significantly influence willingness to participate.
Keywords: Continuing medical education, training needs, blended learning, healthcare workers, traditional medicine.